Labialization in nomatsiguenga - Valqui, Jairo (2011)
This paper uses three different approaches (Generative phonology, Nonlinear phonology and Optimality Theory) in order to describe and explain a phonological process of assimilation called labialization in Nomatsiguenga, that only happens when a labial consonant appears before the central vowel [i]. Standard generative phonology characterized assimilation in terms of features copying. In Nonlinear approach, in contrast, assimilation is characterized as the association of features of segment A to a neighboring segment B. Finally, in Optimality Theory, assimilation is characterized as Markedness constraint called AGREE(x).